1991
DOI: 10.1111/j.1744-7348.1991.tb05649.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of plant viruses by fungi

Abstract: The evidence for the mechanisms involved in virus transmission by fungi is reviewed in relation to the non-persistent and persistent categories usually recognised.Non-persistent transmission by Olpidium spp. has been little studied in the last 20 years, but appears to depend on adsorption of virus to the outside of the fungal zoospores. This seems to be under the genetic control of both the virus (via its coat protein) and the vector. Such viruses are not transmitted in the fungal resting spores. The route by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 45 publications
0
35
0
2
Order By: Relevance
“…bornovanus, and Olpidium transmission of several other small spherical plant viruses, have shown that the transmission process is highly specific (1,6). For example, O. bornovanus transmits CNV but not Tobacco necrosis necrovirus (TNV), and conversely, O. brassicae transmits TNV but not CNV (10,34).…”
mentioning
confidence: 99%
“…bornovanus, and Olpidium transmission of several other small spherical plant viruses, have shown that the transmission process is highly specific (1,6). For example, O. bornovanus transmits CNV but not Tobacco necrosis necrovirus (TNV), and conversely, O. brassicae transmits TNV but not CNV (10,34).…”
mentioning
confidence: 99%
“…Bound virus then enters the cells of plants following the encystment of zoospores on roots (1,4). Several studies have shown that the transmission process is highly specific (1,4). For example, O. brassicae transmits the necrovirus Tobacco necrosis virus (TNV-A) but not the tombusvirus Cucumber necrosis virus (CNV), and conversely, O. bornovanus transmits CNV but not TNV-A (7,30).…”
mentioning
confidence: 99%
“…It has been proposed that transmission occurs following the release of zoospores and virus from different plants into the soil and subsequent adsorption of virus particles onto the surfaces of zoospores. Bound virus then enters the cells of plants following the encystment of zoospores on roots (1,4). Several studies have shown that the transmission process is highly specific (1,4).…”
mentioning
confidence: 99%
“…O SBWMV apresenta genoma de RNA bipartido encapsulado em partículas alongadas retilíneas, de fita simples e senso positivo (Shirako, 1998). A transmissão do vírus ocorre pela colonização dos pêlos radiculares de plantas através dos zoosporos virulíferos de P. graminis, considerado um parasita obrigatório de raízes de gramíneas (Barr, 1979) que pode persistir por longos períodos em raízes em decomposição ou no solo (Adams, 1991). Os sintomas da virose variam de mosaico verde a mosaico amarelo, ocorrendo mais freqüentemente em plantas com desenvolvimento em áreas mais baixas, especialmente durante extensos períodos de frio e alta umidade do solo (Larsen et al, 1985).…”
Section: Introductionunclassified